2023
DOI: 10.1038/s41598-023-35607-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human activities on Sericinus montela and its host plant Aristolochia contorta

Abstract: Sericinus montela, a globally threatened butterfly species, feeds exclusively on Aristolochia contorta (Northern pipevine). Field surveys and glasshouse experiments were conducted to obtain a better understanding of the relationship between the two species. Interviews with the persons concerned with A. contorta were conducted to collect information about the site management measures. We found that management practices to control invasive species and manage the riverine areas might reduce the coverage of A. con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…During asexual reproduction, the plant stores reserves in the root or rhizome and undergoes seasonal changes, shedding its aboveground parts in winter and regrowing new stems from underground buds annually ( Lee, 2012 ). Additionally, the vulnerable butterfly, Sericinus montela , whose larvae feed solely on A. contorta , underscores the importance of conservation studies ( Park et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…During asexual reproduction, the plant stores reserves in the root or rhizome and undergoes seasonal changes, shedding its aboveground parts in winter and regrowing new stems from underground buds annually ( Lee, 2012 ). Additionally, the vulnerable butterfly, Sericinus montela , whose larvae feed solely on A. contorta , underscores the importance of conservation studies ( Park et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the specific herbivory by S. montela is highly destructive to the above-ground parts of A. contorta . The larvae of S. montela hatch in clusters and consume significant portions of the leaves during their growth period [ 31 ]. Direct observations have shown that the leaves near the hatching sites of S. montela are nearly entirely eaten, particularly in small plants, leaving only the stems.…”
Section: Introductionmentioning
confidence: 99%